Algorithm Selection Based on Exploratory Landscape Analysis and Cost-Sensitive Learning - Bischl, Bernd; Mersmann, Olaf; Trautmann, Heike; Preuß, Mike (Proceedings of the 14th Annual Conference on Genetic and Evolutionary Computation)
The steady supply of new optimization methods makes the algorithm selection problem (ASP) an increasingly pressing and challenging task, specially for real-world black-box optimization problems. The introduced approach considers the ASP as a cost-sensitive classification task which is based on Exploratory Landscape Analysis. Low-level features gathered by systematic sampling of the function on the feasible set are used to predict a well-performing algorithm out of a given portfolio. Example-specific label costs are defined by the expected runtime of each candidate algorithm. We use one-sided support vector regression to solve this learning problem. The approach is illustrated by means of the optimization problems and algorithms of the BBOB’09/10 workshop.
Keywords: machine learning; exploratory landscape analysis; fitness landscape; benchmarking; evolutionary optimization; bbob test set; algorithm selection

Local Search and the Traveling Salesman Problem: A Feature-Based Characterization of Problem Hardness - Mersmann, Olaf; Bischl, Bernd; Bossek, Jakob; Trautmann, Heike; Wagner, Markus; Neumann, Frank (Learning and Intelligent Optimization)
With this paper we contribute to the understanding of the success of 2-opt based local search algorithms for solving the traveling salesman problem (TSP). Although 2-opt is widely used in practice, it is hard to understand its success from a theoretical perspective. We take a statistical approach and examine the features of TSP instances that make the problem either hard or easy to solve. As a measure of problem difficulty for 2-opt we use the approximation ratio that it achieves on a given instance. Our investigations point out important features that make TSP instances hard or easy to be approximated by 2-opt.

Resampling Methods in Model Validation - Bischl, B; Mersmann, O; Trautmann, Heike; Weihs, C (Evolutionary Computation Journal)
Meta-modeling has become a crucial tool in solving expensive optimization problems. Much of the work in the past has focused on finding a good regression method to model the fitness function. Examples include classical linear regression, splines, neural networks, Kriging and support vector regression. This paper specifically draws attention to the fact that assessing model accuracy is a crucial aspect in the meta-modeling framework. Resampling strategies such as cross-validation, subsampling, bootstrapping, and nested resampling are prominent methods for model validation and are systematically discussed with respect to possible pitfalls, shortcomings, and specific features. A survey of meta-modeling techniques within evolutionary optimization is provided. In addition, practical examples illustrating some of the pitfalls associated with model selection and performance assessment are presented. Finally, recommendations are given for choosing a model validation technique for a particular setting.

Homogene Approximation der Paretofront bei mehrkriteriellen Kontrollproblemen - Rudolph, G; Trautmann, Heike; Schütze, O (at-Automatisierungstechnik)
Es werden mehrkriterielle evolutio-näre Algorithmen (EMOA) für zwei- und höherdimensio-nale Probleme vorgestellt, die gleichmäßig verteilte Lö-sungen entlang der wahren Paretofront generieren. Diesist insbesondere wichtig im Kontext mehrkriterieller Kon-trollprobleme. Die Methodik beruht auf der Minimierungdes gemittelten Hausdorff-Abstandes in Bezug aufdie Paretofront. Die EMOA-Varianten werden vergleichendzu aktuellen Verfahren auf Benchmarkproblemen getestet.

Local Search and the Traveling Salesman Problem: A Feature-Based Characterization of Problem Hardness - Mersmann, Olaf; Bischl, Bernd; Bossek, Jakob; Trautmann, Heike; Wagner, Markus; Neumann, Frank (Revised Selected Papers of the 6th International Conference on Learning and Intelligent Optimization - Volume 7219)
With this paper we contribute to the understanding of the success of 2-opt based local search algorithms for solving the traveling salesman problem TSP. Although 2-opt is widely used in practice, it is hard to understand its success from a theoretical perspective. We take a statistical approach and examine the features of TSP instances that make the problem either hard or easy to solve. As a measure of problem difficulty for 2-opt we use the approximation ratio that it achieves on a given instance. Our investigations point out important features that make TSP instances hard or easy to be approximated by 2-opt.
Keywords: 2-opt; Classification; Feature Selection; MARS; TSP

Local Search and the Traveling Salesman Problem: A Feature-Based Characterization of Problem Hardness - Mersmann, Olaf; Bischl, Bernd; Bossek, Jakob; Trautmann, Heike; Wagner, Markus; Neumann, Frank (Learning and Intelligent Optimization)
With this paper we contribute to the understanding of the success of 2-opt based local search algorithms for solving the traveling salesman problem (TSP). Although 2-opt is widely used in practice, it is hard to understand its success from a theoretical perspective. We take a statistical approach and examine the features of TSP instances that make the problem either hard or easy to solve. As a measure of problem difficulty for 2-opt we use the approximation ratio that it achieves on a given instance. Our investigations point out important features that make TSP instances hard or easy to be approximated by 2-opt.

SYSTEMC UVM VERIFICATION COMPONENTS - Kuznik, Christoph; Oliveira, Marcio F.; Müller, Wolfgang (Design, Automation and Test in Europe DATE)
We present an enhanced UVM for SystemC library which incorporates verification best practices from OVM-ML and UVM as well as project partner implementations. Moreover, we extended functionality and implemented missing features, such as domain specific components, stimuli sequence generation and management, call-back facilities, response to request routing, transaction recording and many more. Apart from that, we added crucial verification components, such as functional coverage.

Dynamic Load Balancing in Peer-to-Peer Networks - Korzeniowski, Miroslaw

Stackelberg Network Pricing Games - Briest, Patrick; Krysta, Piotr; Hoefer, Martin (Algorithmica)

PADrend: Platform for Algorithm Development and Rendering - Jähn, Claudius; Petring, Ralf; Eikel, Benjamin (Augmented & Virtual Reality in der Produktentstehung)
In dieser Arbeit stellen wir ein flexibles System zur Entwicklung und Evaluation von 3-D-Renderingalgorithmen vor, das die Visualisierung komplexer virtueller Szenen auf einem breiten Spektrum an Geräten erlaubt. Die Aufbereitung und Echtzeitdarstellung solcher virtueller Szenen, wie sie beispielsweise aus detaillierten CAD-Daten erzeugt werden, stellt in vielerlei Hinsicht eine algorithmische und technische Herausforderung dar. Die 3-D-Szenendaten können nach dem Dateiimport aus einem Austauschformat in eine Vielzahl unterschiedlicher Datenstrukturen überführt werden. Es muss ein geeignetes Renderingverfahren ausgewählt und eingestellt werden, welches sowohl die Eigenschaften der Szene (Zahl der Polygone, Grad der Verdeckung etc.) als auch die Fähigkeiten der Hardware berücksichtigt. Auf der einen Seite stellt die Darstellung auf mobilen Endgeräten wie Smartphones besonders hohe Anforderungen aufgrund der Speicherbeschränkung und der geringen Leistungsfähigkeit der Grafikhardware. Auf der anderen Seite stehen bei Großprojektionssystemen, wie beispielsweise dem HD-Visualisierungscenter des Heinz Nixdorf Instituts, die hohe Bildqualität bei stereoskopischer Darstellung und die Unterstützung von Trackingsystemen im Vordergrund. Der Fokus des von uns entwickelten Systems PADrend liegt in der Bereitstellung einer flexiblen und leicht erweiterbaren Grundlage für die Entwicklung und Evaluation von 3-D-Renderingalgorithmen und räumlichen Datenstrukturen im Bereich der Forschung und der universitären Ausbildung. Durch den modularen Aufbau und die große Bandbreite an unterstützten Systemen wird gewährleistet, dass eine Vielzahl unterschiedlicher Entwicklungen und Anwendungen auf PADrend aufsetzen können. In diesem Artikel geben wir einen Überblick über den Aufbau und die Fähigkeiten des Systems. Des Weiteren geben wir ein Beispiel für ein Anwendungsszenario, in dem PADrend eingesetzt wird: die Visualisierung von architektonischen Modellen auf einem Multiprojektionssystem.

Coupled inverted pendulums: A benchmark for evolving decentral controllers in modular robotics - Hamann, Heiko; Schmickl, Thomas; Crailsheim, Karl; Krasnogor, Natalio; Luca Lanzi, Pier (Proceedings of the 13th Annual Genetic and Evolutionary Computation Conference, GECCO 2011)
The challenging scientific field of self-reconfiguring modular robotics (i.e., decentrally controlled 'super-robots' based on autonomous, interacting robot modules with variable morphologies) calls for novel paradigms of designing robot controllers. One option is the approach of evolutionary robotics. In this approach, the challenge is to achieve high evaluation numbers with the available resources which may even affect the feasibility of this approach. Simulations are usually applied at least in a preliminary stage of research to support controller design. However, even simulations are computationally expensive which gets even more burdensome once comprehensive studies and comparisons between different controller designs and approaches have to be done. Hence, a benchmark with low computational cost is needed that still contains the typical challenges of decentral control, is comparable, and easily manageable. We propose such a benchmark and report an empirical study of its characteristics including the transition from the single-robot setting to the multi-robot setting, typical local optima, and properties of adaptive walks through the fitness landscape.

Thermodynamics of Emergence: Langton's Ant Meets Boltzmann - Hamann, Heiko; Schmickl, Thomas; Crailsheim, Karl (IEEE Symposium on Artificial Life (IEEE ALIFE 2011))
The current definitions of emergence have no effects in the context of artificial life that could convincingly be called `constructive'. They are rather descriptive labels or tests. In order to get towards recipes of generating emergence we need to know systemic characteristics that help during the design phase of artificial life systems and worlds. In this paper, we develop and discuss five hypotheses that are not meant to be irrevocable but rather thought-provoking. We introduce two modeling approaches for Langton's ant to clarify these hypotheses. Then we discuss general properties of systems, such as (ir-)reversibility, dependence on initial states, computation, discreetness, and undecidable properties of system states.

Evolving for Creativity: Maximizing Complexity in a Self-organized Multi-particle System - Hamann, Heiko; Schmickl, Thomas; Crailsheim, Karl (10th European Conference on Artificial Life (ECAL'09))

Robotic Organisms: Artificial Homeostatic Hormone System and Virtual Embryogenesis as Examples for Adaptive Reaction-Diffusion Controllers - Hamann, Heiko; Schmickl, Thomas; Stradner, Jürgen; Crailsheim, Karl; Thenius, Rona; Fitch, Robert (Robotic Organisms: Artificial Homeostatic Hormone System and Virtual Embryogenesis as Examples)

BEECLUST: A Swarm Algorithm Derived from Honeybees - Hamann, Heiko; Schmickl, Thomas (Bio-inspired Computing and Communication Networks)

Evolving a novel bio-inspired controller in reconfigurable robots - Hamann, Heiko; Karsai, Istvan; Schmickl, Thomas; Stradner, Jürgen; Crailsheim, Karl; Thenius, Ronald; Kampis, Gyoergy; Szathmary, Eoers (Advances in Artificial Life, 10th European Conference, ECAL 2009)

Embodiment of Honeybee's Thermotaxis in a Mobile Robot Swarm - Hamann, Heiko; Schmickl, Thomas; Crailsheim, Karl; Thenius, Ronald; Kengyel, Daniela (10th European Conference on Artificial Life (ECAL'09))

Explaining Emergent Behavior in a Swarm System Based on an Inversion of the Fluctuation Theorem - Hamann, Heiko; Schmickl, Thomas; Crailsheim, Karl (Advances in Artificial Life, ECAL 2011: Proceedings of the 11th European Conference on the Synthesis and Simulation of Living Systems)

Major Feedback Loops Supporting Artificial Evolution in Multi-modular Robotics - Hamann, Heiko; Schmickl, Thomas; Stradner, Jürgen; Crailsheim, Karl; Winkler, Lutz (New Horizons in Evolutionary Robotics)

Modelling a hormone-inspired controller for individual- and multi-modular robotic systems - Schmickl, Thomas; Hamann, Heiko; Crailsheim, Karl (Mathematical and Computer Modelling of Dynamical Systems)

Bicriteria-Approximation für das k-Median-Clustering mit Bregman-Divergenzen - Böttger, Timm

Implementation of a Singular Value Decomposition Module on an FPGA - Hosseinimehr, Masoud; Montealegre, Norma (The 23rd IASTED International Conference on Parallel and Distributed Computing and Systems (PDCS 2011))

Automatic Feature Classification for Object Detection based on Motion Analysis - Jungmann, Alexander; Kleinjohann, Bernd (Proceedings of the 5th International Conference on Automation, Robotics and Applications (ICARA))
In this paper an approach for automatic feature classification based on their motion in the image plane is introduced. By combining concepts of the human perception of motion with techniques belonging to the area of cluster analysis, we subsequently abstract the visual data in order to separate features, whose motion is caused by the sensor motion from features, which possibly belong to dynamic objects in the environment. The presented algorithm exclusively works on data, that can be extracted from the two dimensional image plane. Hence, no external data like the current motion of the applied camera is required. Furthermore, the algorithm works on any type of tracked feature, as long as it can be statistically represented. The results of the presented approach constitute a very good starting point for additional object detection mechanisms.

Towards Using Virtual Forces for Image Registration - Stern, Claudius; Rasche, Christoph; Kleinjohann, Lisa; Kleinjohann, Bernd (The 5th International Conference on Automation, Robotics and Applications (ICARA 2011))
This paper introduces a novel method for registering a large amount of aerial images when camera parameters are almost unknown and no reference images are available. The envisioned application is the creation of an overview map of a disaster area from images made by unmanned aerial vehicles (UAVs) equipped with cameras. The camera systems only have uncertain information about flight attitude. With traditional methods, the relatively small perspective errors per image sum up over time resulting in perspective errors which prevent building a consistent map from successively arriving images. By using virtual forces between images, the image parameters are continuously adapted to the current map. The small projective errors of quasi orthographic images are distributed among overlapping images. Having UAVs which deliver quasi orthographic images, our approach can build a contemporary overview without the need to have all images in advance.

How to manage and Search/Retrieve Information Objects - Dannewitz, Christian; al, et (Architecture and Design for the Future Internet)

Integrating Generic Paths and NetInf - Dannewitz, Christian; al, et (Architecture and Design for the Future Internet)

A Distributed Multi-UAV Path Planning Approach for 3D Environments - Rasche, Christoph; Stern, Claudius; Kleinjohann, Lisa; Kleinjohann, Bernd (The 5th International Conference on Automation, Robotics and Applications (ICARA 2011))
During rescue scenarios it is indispensable to obtain an overview of the situation. Unmanned aerial vehicles (UAVs) can gather the necessary information in a fast and efficient way. This paper presents an approach for path planning in 3D environments offering a solution to explore disaster areas including, e.g., partially or completely destroyed buildings. Using multiple UAVs decreases the time needed to receive a complete overview if the problem of coordination and task allocation is solved. We present an approach for the use of multiple UAVs. The UAVs work in a distributed manner without any central coordination instance and cover the exploration of terrains as well as goal-oriented path planning. When using multiple UAVs redundant exploration is avoided through the use of inter-UAV-communication. The approach is based on potential fields and uses the simplicity of the gradient method to calculate paths for fast exploration of the terrain.

A Bio-inspired Coverage and Connectivity Maintenance Algorithm - Mathews, Emi; Graf, Tobias; Kulathunga, K. S. S. B. (Sixth International ICST Conference on Bio-Inspired Models of Network, Information, and Computing Systems)

Aspect enhanced functional coverage driven verification in the SystemC HDVL - Kuznik, Christoph; Müller, Wolfgang (Proc. of the 8th International SoC Design Conference 2011 (ISOCC 2011))

IP-XACT based System Level Mutation Testing - Xie, Tao; Müller, Wolfgang (Proceedings of the 16th IEEE International High Level Design Validation and Test Workshop (HLDVT))

Model-driven runtime resource predictions for advanced mechatronic systems with dynamic data structures - Henkler, Stefan; Oberthür, Simon; Giese, Holger; Seibel, Andreas (International Journal of Computer Systems Science & Engineering 26 (6))

Enabling Constraint-based Binary Reconfiguration by Binary Analysis - Baldin, Daniel; Grösbrink, Stefan; Oberthür, Simon (International Journal on Computing (JoC) 1(4))

F-DRARE: A Framework for Deterministic runtime adaptation of Cyber Physical Systems - Bin Tariq, Fahad (1st International Workshop on Adaptive Services for the Future Internet, 4th European Conference, ServiceWave 2011)

High-Level Construction of Emergent Self-Organizing Behavior in Massively Distributed Embedded Systems - Orfanus, Dalimir; Janacik, Peter; Eliassen, Frank; Orten, Pal (Proceedings of Third World Congress on Nature and Biologically Inspired Computing (NaBIC2011))

HDL-Mutation Based Simulation Data Generation by Propagation Guided Search - Xie, Tao; Müller, Wolfgang (Proceedings of the 14th Euromicro Conference on Digital System Design (DSD))

A Test Bed for Investigating Self-X Properties in Multi-Robot Societies - Jungmann, Alexander; Lutterbeck, Jan; Werdehausen, Benjamin; Kleinjohann, Bernd (Proceedings of the 9th IEEE International Conference on Industrial Informatics (INDIN))
In this paper, we introduce a test bed for demonstrating and investigating self-x properties, such as self-optimization and self-organization, within the scope of multi-robot societies under realistic conditions. By doing so, we shift the investigation and demonstration of biologically inspired mechanisms from the simulative point of view to a dynamic and more complex realistic environment. For this purpose, we developed a controlled real-world environment to overcome common problems such as self-localization. Furthermore, we elaborated a concept for a descriptive robotic real-world game. By means of this game, we provide an instrument, which is easily accessible for any kind of audience on the one hand, while it still leaves enough space for an extensive scientific investigation on the other hand.

Miniature Robot BeBot: Mechatronic Test Platform for Self-X Properties - Gausemeier, Jürgen; Schierbaum, Thomas; Dumitrescu, Roman; Herbrechtsmeier, Stefan; Jungmann, Alexander (Proceedings of the 9th IEEE International Conference on Industrial Informatics (INDIN))
Machines are omnipresent. They produce, they transport. Machines facilitate work and assist. The increasing penetration of mechanical engineering by information technology enables considerable benefits. We refer to such systems as advanced mechatronic systems, which relay on the close interaction of mechanics, electric/electronics, control engineering and software engineering. Hence, the design and production of such systems is an interdisciplinary and complex task. Our ambition is a new school for the design of advanced mechatronic systems. Consequently, we need an avant-garde basic system which can be used to develop and to test future applications. The miniature robot BeBot is such a basic system. This robot constitutes the test bench for the applications, being based on modern approaches, such as self-optimization, self-organization and self-coordination as well as on the use of new manufacturing technologies.

Comparison of periodic and aperiodic task models for cyber-physical-systems - Thuy, Andreas (Reconfigurable Communication-centric Systems-on-Chip (ReCoSoC), 2011 6th International Workshop on)

Verification Closure of SystemC Designs with Functional Coverage - Kuznik, Christoph; Müller, Wolfgang (North American SystemC User Group Meeting (16th))
In the area of dynamic verification of virtual prototypes, functional coverage is a valuable tool for answering the "Are we done?" question and achieving verification closure. Recent verification methodologies such as OVM and UVM contain multi-language support that provides a basic SystemC version. However, due to language shortcoming they cannot be utilized for the same amount of verification tasks in the SystemC ecosystem as in other supported hardware design and verification languages. In this presentation, we propose to boost the verification capabilities of SystemC by implementing functional coverage collection and evaluation according to the same metric as defined in the widely accepted IEEE-1800 SystemVerilog cover group feature. We implement a functional coverage library to enable coverage-driven verification of SystemC designs on multiple levels of abstraction enabling value, transition, and expression coverage. To our knowledge, the overall functionalities are not available in the IEEE-1666 SystemC standard or the SCV add-on library, nor are they complete compared to the aforementioned in any publicly available SystemC library.

A Localized Planarization Algorithm for Realistic Wireless Networks - Mathews, Emi; Frey, Hannes (IEEE International Symposium on a World of Wireless, Mobile and Multimedia Networks (WoWMoM))
Planar graph routing works provably correct if the underlying network graph is connected and planar. Typically, wireless networks modeled as 2D graphs, are not planar and planar graph routing applied on such unprocessed network graphs may fail. Planarizing a given connected graph by removing intersecting links might be impossible if the outcome still needs to be a connected subgraph. It becomes even more difficult with distributed planarization techniques, where each node is allowed to use only the information about its local neighborhood. Furthermore, it is getting complicated if the nodes' assigned positions do not reflect the exact physical location. With or without exact location information, the outcome might be disconnected, nonplanar, or both of it. With all these unsolvable problems, the question arises how to apply planar graph routing in a realistic network setting? Fortunately, wireless network graphs bear one property which distinguishes them from arbitrary graphs: due to limited communication range, network links cannot become arbitrarily long. In this work we exploit this locality property to build a new localized planarization algorithm, which is location fault tolerant and which produces planar connected graphs in most cases in realistic wireless models. We evaluate our algorithm using the Log Normal Shadowing model and show that our algorithm always produces planar connected graphs in all simulations even when large location errors are present.

Virtual Prototyping softwareintensiver mechatronischer Systeme Eine Fallstudie - Becker, Markus; Zabel, Henning; Müller, Wolfgang; Elfeky, Ahmed; DiPasquale, Anthony (8. Paderborner Workshop Entwurf mechatronischer Systeme, Band 294)

Coordinated Exploration and Goal-Oriented Path Planning using Multiple UAVs - Rasche, Christoph; Stern, Claudius; Kleinjohann, Lisa; Kleinjohann, Bernd (ThinkMind, International Journal On Advances in Software 3 (3&4))

Self-Organized Cooperation in Swarm Robotics - Khaluf, Yara; Mathews, Emi; Rammig, Franz-Josef (14th IEEE International Symposium on Object/Component/Service-Oriented Real-Time Distributed Computing Workshops (ISORCW))

A Reconfiguration Approach for Fault-Tolerant FlexRay Networks - Klobedanz, Kay; König, A.; Müller, Wolfgang (Proceedings of Design, Automation, Test Europe - DATE2011)

Self-Reconfiguration for Fault-Tolerant FlexRay Networks - Klobedanz, Kay; König, A.; Müller, Wolfgang; Rettberg, Achim (Second IEEE Workshop on Self-Organizing Real-Time Systems - SORT 2011)

Functional Coverage-driven Verification with SystemC on Multiple Level of Abstraction - Kuznik, Christoph; Müller, Wolfgang (Proceedings of DVCON)
SystemC is a versatile C++ based design and verification language, offering various mechanisms and constructs required for embedded systems modeling. Using the add-on SystemC Verification Library (SCV) elemental constrained-random stimuli techniques may be used for verification. However, SCV has several drawbacks such as lack of a functional coverage facility supporting coverage collection on RTL and TLM models. In this article we present a functional coverage library which implements parts of the IEEE 1800-2005 SystemVerilog standard capturing functional coverage throughout the design and verification process, and allows to facilitate coverage-driven verification in SystemC.

A Retargetable SysML-based Front-End for High-Level Synthesis - Mischkalla, Fabian; He, Da; Müller, Wolfgang (Proceedings of 2nd Workshop on Model Based Engineering for Embedded Systems Design (M-BED))
UML profiles like SysML and MARTE have been a major research topic in electronic system design, but are mainly applied for specification and analysis in early design phases. High-Level Synthesis (HLS), however, addresses the physical implementation aspect of electronic systems, and thus leads to different requirements on the accuracy of models. For this, modular interfaces are a novel object-oriented synthesizable technique to overcome the conflict between a higher degree of abstraction and necessary details for further synthesis. In this paper, we present our approach to use SysML as an adequate modeling language for modular interfaces and C/C++/SystemC-based HLS. We extended SysML with annotations for synthesizable SystemC and high-level synthesis constraints and implemented a code generation scheme to achieve design flow automation. Based on the SysML editor Artisan Studio and an industrial case study, we demonstrate the applicability of SysML as a retargetable front-end for HLS design flows.

A SysML-based Framework with QEMU-SystemC Code Generation - He, Da; Mischkalla, Fabian; Müller, Wolfgang (Proceedings of 1st international QEMU Users Forum)

QEMU/SystemC Cosimulation at Different Abstraction Levels - Becker, Markus (1st International QEMU Users Forum (QUF'11))

Hybrid Planning for Self-Optimization in Railbound Mechatronic Systems - Adelt, Philipp; Esau, Natascha; Hölscher, Christian; Kleinjohann, Bernd; Kleinjohann, Lisa; Krüger, Martin; Zimmer, Detmar (Intelligent Mechatronics; Kapitel 10)

Synchronisation eines SystemC Restbus-Simulators mit einem Hardware-In-the-Loop FlexRay Netzwerk - Gnokam Defo, Gilles Bertrand; Müller, Wolfgang (Methoden und Beschreibungssprachen zur Modellierung und Verifikation von Schaltungen und Systemen (MBMV))

Pattern-Based Modeling and Formalizing of Business Process Quality Constraints - Khaluf, Lial; Gerth, Christian; Engels, Gregor (Proceedings of the 23rd international conference on Advanced information systems engineering (CAiSE'11))

Native binary mutation analysis for embedded software and virtual prototypes in SystemC - Kuznik, Christoph; Müller, Wolfgang (Proceedings of the 17th IEEE Pacific Rim International Symposium on Dependable Computing)
Mutation analysis is a powerful tool for white-box testing of the verification environment in order to produce dependable and higher quality software products. However, due to high computational costs and the focus on high-level software languages such as Java mutation analysis is not yet widely used in commercial design flows targeting embedded (software) systems. Here the industry is modeling both hardware and related software parts at higher levels of abstraction, called virtual prototypes, to accelerate parallel development and shorten time-to-market. In this paper we propose a mutation testing verification flow for SystemC based virtual prototypes that may not rely on source code only but on annotated basic blocks and enables mutant creation at assembler level to heavily reduce execution costs and equivalence mutants likelihood.

Emotional Robot Competence and Its Use in Robot Behavior Control - Esau, Natascha; Kleinjohann, Lisa (Emotional Engineering)

Towards a Real-World Scenario for Investigating Organic Computing Principles in Heterogeneous Societies of Robots - Jungmann, Alexander; Lutterbeck, Jan; Werdehausen, Benjamin; Kleinjohann, Bernd; Kleinjohann, Lisa (Proceedings of the 2011 workshop on Organic computing)
In this paper we introduce an infrastructure for investigating Organic Computing principles such as self-optimization and self-organization in real-world scenarios based on a heterogeneous society of robots. This infrastructure, the R3PB-Workbench (Remote Real Robots at the University of Paderborn), provides a controlled environment for conducting real-world multi robot experiments, while relieving the developer from common problems like getting a global view of the entire environment and self-localization within this environment. In addition, it provides a communication layer that hides the heterogeneity of the controlled robot types and also facilitates access to each robot's subjective view. Currently we provide three types of mobile robots with different size and capabilities. Since the workbench is easily customizable, it supports the integration of additional types of robots. Hence, the degree of heterogeneity of the robot group conducting the experiments in the scope of our real-world scenario can be modified as needed. Furthermore, we elaborated a multi-robot game as an illustrative real-world scenario, which on the one hand allows for sophisticated scientific investigations and on the other hand is also appealing for an audience, even with little technical background.

A Fast Hierarchical Learning Approach for Autonomous Robots - Jungmann, Alexander; Kleinjohann, Bernd; Richert, Willi (Organic Computing A Paradigm Shift for Complex Systems, Autonomic Systems)
In this article we present an approach that enables robots to learn how to act and react robustly in continuous and noisy environments while not loosing track of the overall feasibility, i.e. minimising the execution time in order to keep up continuous learning. We do so by combining reinforcement learning mechanisms with techniques belonging to the field of multivariate statistics on three different levels of abstraction: the motivation layer and the two simultaneously learning strategy and skill layers. The motivation layer allows for modelling occasionally contradicting goals in terms of drives in a very intuitive fashion. A drive represents one single goal, that a robot wants to be satisfied, like charging its battery, when it is nearly exhausted, or transporting an object to a target position. The strategy layer encapsulates the main reinforcement learning algorithm based on an abstracted and dynamically adjusted Markovian state space. By means of state abstraction, we minimise the overall state space size in order to ensure feasibility of the learning process in a dynamically changing environment. The skill layer finally realises a generalised learning method for learning reactive low-level behaviours, that enable a robot to interact with the environment.

Increasing Learning Speed by Imitation in Multi-robot Societies - Jungmann, Alexander; Kleinjohann, Bernd; Richert, Willi (Organic Computing A Paradigm Shift for Complex Systems, Autonomic Systems, Band 1)
The paradigm of imitation provides a powerful means for increasing the overall learning speed in a group of robots. While separately exploring the environment in order to learn how to behave with respect to a pre-defined goal, a robot gathers experience based on its own actions and interactions with the surroundings, respectively. By accumulating additional experience via observing the behaviour of other robots, the learning process can be significantly improved in terms of speed and quality. Within this article we present an approach, that enables robots in a multi-robot society to imitate any other available robot without imposing unnecessary restrictions regarding the robots design. Therefore, it benefits not only from its own actions, but also from actions that an observed robot performs. In order to realise the imitation paradigm, we solve three main challenges, namely enabling a robot to decide whom and when to imitate, to interpret and thereby understand the behaviour of an observed robot, and to integrate the experience gathered by observation into its individual learning process.

Back to the Roots of Genres: Text Classification by Language Function - Wachsmuth, Henning; Bujna, Kathrin (Proceedings of 5th International Joint Conference on Natural Language Processing)

Constructing Efficient Information Extraction Pipelines - Wachsmuth, Henning; Stein, Benno; Engels, Gregor (20th ACM International Conference on Information and Knowledge Management)

The Monotone Complexity of Computing k-Clique on Random Graphs - Märtens, Marcus

Algorithms for lattice problems with respect to general norms - Naewe, Stefanie

Hardness and Non-Approximability of Bregman Clustering Problems. - Ackermann, Marcel R; Blömer, Johannes; Scholz, Christoph

How to Share a Secret - Blömer, Johannes (Algorithms Unplugged)

Solving the Closest Vector Problem with respect to Lp Norms - Blömer, Johannes; Naewe, Stefanie (arXiv:1104.3720)
In this paper, we present a deterministic algorithm for the closest vector problem for all l_p-norms, 1 < p < ∞, and all polyhedral norms, especially for the l_1-norm and the l_{∞}-norm. We achieve our results by introducing a new lattice problem, the lattice membership problem. We describe a deterministic algorithm for the lattice membership problem, which is a generalization of Lenstra's algorithm for integer programming. We also describe a polynomial time reduction from the closest vector problem to the lattice membership problem. This approach leads to a deterministic algorithm that solves the closest vector problem for all l_p-norms, 1 < p < ∞, in time p log_2 (r)^{O (1)} n^{(5/2+o(1))n} and for all polyhedral norms in time (s log_2 (r))^{O (1)} n^{(2+o(1))n}, where s is the number of constraints defining the polytope and r is an upper bound on the coefficients used to describe the convex body.

Short Signatures from Weaker Assumptions - Hofheinz, Dennis; Jager, Tibor; Kiltz, Eike (Advances in Cryptology - ASIACRYPT 2011 - 17th International Conference on the Theory and Application of Cryptology and Information Security, Seoul, South Korea, December 4-8, 2011. Proceedings)

How to break XML encryption - Jager, Tibor; Somorovsky, Juraj (Proceedings of the 18th ACM Conference on Computer and Communications Security, CCS 2011, Chicago, Illinois, USA, October 17-21, 2011)

Bounded Retransmission in Event-B{\(\parallel\)}CSP: a Case Study - Schneider, Steve; Treharne, Helen; Wehrheim, Heike (Electr. Notes Theor. Comput. Sci.)

Mechanically verified proof obligations for linearizability - Derrick, John; Schellhorn, Gerhard; Wehrheim, Heike (ACM Trans. Program. Lang. Syst.)

ReL: A Generic Refactoring Language for Specification and Execution - Ruhroth, Thomas; Wehrheim, Heike; Ziegert, Steffen (37th EUROMICRO Conference on Software Engineering and Advanced Applications, SEAA 2011, Oulu, Finland, August 30 - September 2, 2011)

Verifying Linearisability with Potential Linearisation Points - Derrick, John; Schellhorn, Gerhard; Wehrheim, Heike (FM 2011: Formal Methods - 17th International Symposium on Formal Methods, Limerick, Ireland, June 20-24, 2011. Proceedings)

Sound and Complete Abstract Graph Transformation - Steenken, Dominik; Wehrheim, Heike; Wonisch, Daniel (Formal Methods, Foundations and Applications - 14th Brazilian Symposium, SBMF 2011, São Paulo, Brazil, September 26-30, 2011, Revised Selected Papers)

A CSP Account of Event-B Refinement - Schneider, Steve; Treharne, Helen; Wehrheim, Heike (Proceedings 15th International Refinement Workshop, Refine@FM 2011, Limerick, Ireland, 20th June 2011.)

Multi-touch, tangible and pen-based interaction in incident planning - Nebe, Karsten; Fischer, Holger Gerhard; Klompmaker, Florian; Jung, Helge

Virtual Learning Spaces for Co-Active Learning - Keil, Reinhard; Selke, Harald (Proc. of Int. Conf. on Improving University Teaching)
Kollaboratives Lernen kann im Großen und Ganzen durch verteilte, unterbrochene kooperative Prozesse charakterisiert werden, da die Interaktion mit anderen Lernern und Lehrenden zu verschiedenen Zeiten an verschiedenen Orten stattfindet. Um die zeitlich und räumlich verteilten Lernaktivitäten zu integrieren, muss ein virtueller Lernraum bereitgestellt werden der einerseits als Arena kooperativer Interaktionen dient und andererseits gleichzeitig ein verteiltes externes Gedächtnis durch persistente Lernobjekte bietet. Das Konzept des ko-aktiven Lernens umfasst eine Vielzahl von technischen Konzepten und Funktionen, die kollaboratives Lernen in unterschiedlichsten Lernarrangements unterstützen.

Multi-Touch Interaction for Disaster Management.} - Paelke, Volker; Nebe, Karsten; Klompmaker, Florian; Jung, Helge

Hypothesis- guided technology design as the basis of contextual computer science - Keil, Reinhard

Smart Fiducials: Advanced Tangible Interaction Techniques through Dynamic Visual Paterns - Klompmaker, Florian; Nebe, Karsten; Jung, H

User Centered Design Process of OSAMI-D: Developing User Interfaces for a Remote Ergometer Training Application - Klompmaker, Florian; Nebe, Karsten; Busch, Clemens; Willemsen, Detlev (Proceedings of the International Conference on Health Informatics)

KoProV: A Learning Approach for Coordinated Learning of Modeling and Simulation Based on Knowledge Modules - Laroque, Christoph; Schulte, Jonas (Proceedings of the 2011 Spring Simulation Multiconference)

WasabiBeans - Web Application Services and Business Integration - Schulte, Jonas (Proceedings of the 13th International Conference on Enterprise Information Systems, SciTePress - Science and Technology Publications, Beijing, China)

Computer scientists, ergonomists and chemists are shaping the future. E-Portofolios support {\ "u} the flow rate in education and training - Rudolph, S; Niehus, Dominik

Koi School - Towards the Next Level of Communication, Organization and Integration in Education - Schulte, Jonas; Keil, Reinhard; Klaholt, D; Sauer, J (Proceedings of the 13th International Conference on Enterprise Information Systems, SciTePress - Science and Technology Publications, Beijing, China)

Support {\ "u} support of the co-active research discourse through synergies between e-learning and e-science - Schulte, Jonas; Keil, Reinhard; Oberhoff, Andreas

Laboratory 2.0 - Towards and Integrated Research Environment for Engineering Mechanics - Schulte, Jonas; Keil, Reinhard; Rybka, Johann; Ferber, Ferdinand (Proceedings of the 13th International Conference on Enterprise Information Systems, SciTePress - Science and Technology Publications, Bejing, China)

KoForum - Cooperative research environment for {\ "u} for cross-organizational scientific Laboratory work - Schulte, Jonas; Rybka, Johann; Ferber, Ferdinand; Keil, Reinhard

Semantic Positioning - Supporting Knowledge Work through Semantic Spatial Arrangements - Erren, Patrick

A Holistic Model for Integrating Usability Engineering and Software Engineering Enriched with Marketing Activities - Fischer, Holger Gerhard; Nebe, Karsten; Klompmaker, Florian

Authenticated entries on multi-touch tables - Jung, Helge; Nebe, Karsten; Klompmaker, Florian; Fischer, Holger Gerhard

Exploiting New Interaction Techniques for Disaster Control Management using Multitouch-, Tangible- and Pen-based-Interaction - Nebe, Karsten; Klompmaker, Florian; Jung, Helge; Fischer, Holger Gerhard

Der Qualit {\ "a} tsstandard f ü r Usability engineering of the German UPA: Current status of the work - Fischer, Holger Gerhard; Bogner, Christian; Geis, Thomas; Polkehn, Knut; Zimmermann, Dirk

Automatic Validation and Correction of Formalized, Textual Requirements - Holtmann, Jörg; Meyer, Jan; von Detten, Markus (2011 IEEE Fourth International Conference on Software Testing, Verification and Validation Workshops)
Nowadays requirements are mostly specified in unrestricted natural language so that each stakeholder understands them. To ensure high quality and to avoid misunderstandings, the requirements have to be validated. Because of the ambiguity of natural language and the resulting absence of an automatic mechanism, this has to be done manually. Such manual validation techniques are timeconsuming, error-prone, and repetitive because hundreds or thousands of requirements must be checked. With an automatic validation the requirements engineering process can be faster and can produce requirements of higher quality. To realize an automatism, we propose a controlled natural language (CNL) for the documentation of requirements. On basis of the CNL, a concept for an automatic requirements validation is developed for the identification of inconsistencies and incomplete requirements. Additionally, automated correction operations for such defective requirements are presented. The approach improves the quality of the requirements and therefore the quality of the whole development process.

Eine durchgängige Entwicklungsmethode von der Systemarchitektur bis zur Softwarearchitektur mit AUTOSAR - Meyer, Jan; Holtmann, Jörg (Tagungsband des Dagstuhl-Workshop MBEES: Modellbasierte Entwicklung eingebetteter Systeme VII)
Heutige Steuergeraete im Automobilbereich zeichnen sich durch eine hohe Funktionsvielfalt und eine hohe Vernetzung untereinander aus. Dies fuehrt zu immer komplexeren Systemen, wobei auch immer mehr sicherheitskritische Funktionen durch Software realisiert werden. Damit die Qualitaet der Software entsprechend hoch und zufriedenstellend ist, erfordert die Entwicklung ein systematisches und prozesskonformes Vorgehen. Der fuer die Softwarearchitektur entwickelte AUTOSAR Standard ist allerdings nicht fuer die fruehen Entwicklungsphasen wie die Anforderungsanalyse und das Systemarchitekturdesign gedacht, welche von Prozessbewertungsmodellen – wie Automotive SPICE – gefordert werden. Als Loesung fuer die Analyse bietet sich die Nutzung der Systems Modeling Language (SysML) mit Anpassungen bzw. Erweiterungen an die Beduerfnisse der Automobilindustrie, an. Damit aber keine Luecke im Entwicklungsprozess entsteht, wird bei der hier vorgestellten Methode ein wohldefinierter uebergang zur AUTOSAR Architektur, und zwar zur Applikations- und zur Basissoftware, definiert.

Interpreting Story Diagrams for the Static Detection of Software Patterns - Fockel, Markus; Travkin, Dietrich; von Detten, Markus (Proceedings of the 8th International Fujaba Days)
Software maintenance tasks require knowledge about the software’s design. Several tools help to identify implementations of software patterns, e.g. Design Patterns, in source code and thus help to reveal the underlying design. In case of the reverse engineering tool suite Reclipse, detection algorithms are generated from manually created, formal pattern specifications. Due to numerous variants that have to be considered, the pattern specification is error-prone. Because of this, the complex, step-wise generation process has to be traceable backwards to identify specification mistakes. To increase the traceability, we directly interpret the detection algorithm models (story diagrams) instead of executing code generated from these models. This way, a reverse engineer no longer has to relate generated code to the story diagrams to find mistakes in pattern specifications.

Approximative occlusion culling using the hull tree - Suess, Tim; Koch, Clemens; Jähn, Claudius; Fischer, Matthias (Proceedings of the Graphics Interface 2011 Conference, May 25-27, St. John's, Newfoundland, Canada)
Occlusion culling is a common approach to accelerate real-time rendering of polygonal 3D-scenes by reducing the rendering load. Especially for large scenes, it is necessary to remove occluded objects to achieve a frame rate that provides an interactive environment. In order to benefit from the culling properly, often hierarchical data structures are used. These data structures typically create a spatial subdivision of a given scene into axis-aligned bounding boxes. These boxes can be tested quickly, but they are not very precise. By using these boxes, the included objects are detected as visible, even if other objects occlude them (false-positives). To get perfect results, the models original geometry included in the box has to be tested, but this would require too much computational power. To overcome this problem, original objects approximations could be used, but typical methods for mesh simplification cannot be applied, because they do not create an outer hull for a given object. We present a model simplification algorithm, which generates simple outer hulls, consisting of only few more triangles than a box, while preserving an objects shape better than a corresponding bounding box. This approach is then extended to a hierarchical data structure, the so-called hull tree, that can be generated for a given scene to improve the visibility tests. Next, we present an approximative rendering algorithm, which combines the features of the hull tree with the use of inner hulls for efficient occlusion detection and global state-sorting of the visible objects.

Simulation aided, knowledge based routing for AGVs in a distribution warehouse - Klaas, Alexander; Laroque, Christoph; Dangelmaier, Wilhelm; Fischer, Matthias (Proceedings of the 2011 Winter Simulation Conference (WSC))

Ein paralleles Out-of-Core Renderingsystem für Standard-Rechnernetze - Suess, Tim; Jähn, Claudius; Fischer, Matthias; Meyer auf der Heide, Friedhelm; Koch, Clemens (Augmented & Virtual Reality in der Produktentstehung)

Parallel Real-Time Rendering using Heterogeneous PC Clusters - Suess, Tim

Competitive and Fair Medium Access Despite Reactive Jamming - W. Richa, Andrea; Scheideler, Christian; Schmid, Stefan; Zhang, Jin (2011 International Conference on Distributed Computing Systems, ICDCS 2011, Minneapolis, Minnesota, USA, June 20-24, 2011)

Towards jamming-resistant and competitive medium access in the SINR model - W. Richa, Andrea; Scheideler, Christian; Schmid, Stefan; Zhang, Jin (Proceedings of the 3rd ACM workshop on Wireless of the students, by the students, for the students, S3@MOBICOM 2011, Las Vegas, NV, USA, September 19 - 23, 2011)

Self-stabilizing leader election for single-hop wireless networks despite jamming - W. Richa, Andrea; Scheideler, Christian; Schmid, Stefan; Zhang, Jin (Proceedings of the 12th ACM Interational Symposium on Mobile Ad Hoc Networking and Computing, MobiHoc 2011, Paris, France, May 16-20, 2011)